Observation Duration and Multipath Analysis on Yogyakarta Opak Fault Monitoring Stations - Widjajanti, Nurrohmat; Setyawan, Afradon Aditya; Sunantyo, Aris; Parseno, Parseno (2018)
GNSS observations of Opak Fault are performed on the monitoring network from 2013 to 2016 to find out the deformation magnitude. The condition around the monitoring Bench Marks (BMs) change with the time. The growing vegetations make the GNSS observation data have a different obstruction and multipath values. In addition, the observation performed each year has different observation duration. In this study, the difference in observation duration and multipath value in each year is modeled by linear and polynomial regressions. The modeling is carried out to determine the relationship between observation duration and multipath values to the coordinate precisions. The observation duration and multipath values are grouped into several classes to simplify the modeling. Based on the result, it is shown that the observation durations have higher effect to the coordinate precision than multipath value.